Prediction of benign and malignant pulmonary nodules using preoperative CT features: using PNI-GARS as a predictor - Zhan, Yuxin; Song, Feipeng; Zhang, Wenjia; Gong, Tong; Zhao, Shuai; Lv, Fajin (Frontiers in Immunology, 2024)
PurposeThe aim of this study was to develop and validate a prediction model for classification of pulmonary nodules based on preoperative CT imaging.Materials and methodsA data set of Centers 1 (training set: 2633; internal testing set: 1129); Center 2 and Center 3 (external testing set: 218) of patients with pulmonary nodule cases was retrospectively collected. Handcrafted features were extracted from noncontrast chest CT scans by three senior radiologists. A total of 22 clinically handcrafted parameters (age, gender, L-RADS, and PNI-GARS et al.) were used to construct machine learning models (random forest, gradient boosting, and explainable boosting) for the classification of preoperative pulmonary nodules, and the parameters of the model were adjusted to achieve optimal performance. To evaluate the prediction capacity of each model. Both 5-fold cross-validation and 10-fold cross-validation were used to test the robustness of the models.ResultsThe explainable boosting model had the best performance on our constructed data. The model achieves an accuracy of 89.9%, a precision of 97.48%, a specificity of 89.5%, a sensitivity of 91.1%, and an AUC of 90.3%. In human-machine comparison, the AUC of machine learning models (90.4%, 95% CI: 85.5%–94.8%) was significantly improved compared to radiologists (60%, 95% CI: 50%–71.4%).ConclusionsThe explainable boosting model exhibited superior performance on our dataset, achieving high accuracy and precision in the diagnosis of pulmonary nodules compared to experienced radiologists.